Feasibility Analysis of Investment Project Addition of Printing Machine with Capital Budgeting Method in Aulia Mandiri Printing - Faisol Agung Ruditiawan (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study aims to analyze Aulia Mandiri Printing in making investments or procurement of fixed assets in order to maintain the stability of production and produce more printing products so that consumer demands can be met.The source of data in this study is a financial statement consisting of a 2021 income statement. This type of research is descriptive quantitative.The types of data in this study are primary and secondary data. While the data analysis method used is projection with measurement and forecasting methods which are then used to calculate investment feasibility.